TERJEMAHAN NOVEL KARYA SOETHAMA DARI BAHASA INDONESIA KE DALAM BAHASA INGGRIS: PENGURANGAN DAN PENAMBAHAN MAKNA DALAM PENERJEMAHAN - Dian Susanthi I Gusti Ayu Agung; Pratama Agus Darma Yoga; Jayantini I Gusti Agung Sri Rwa; Nurwahyuni Kiki (KULTURISTIK: Jurnal Bahasa dan Budaya, 2022)
Research on translation, especially related to loss and gain of information in translation, in recent years has been carried out quite often. However, these studies are still focused on studying the structure (grammatical error). In this regard, this study aims to examine the loss and gain of information in translation which not only focuses on grammatical errors, but also discusses the loss and gain of information that occurs in the translation process in the source book entitled "Mandi Api" and its translation "Ordeal by Fire". The selected books were written by Balinese writers and translated into English by an American translator. In this regard, this study examines the phenomenon of gain of information and loss of information in translating text from SL to SL. This study analyzes the meaning of translation from SL into TL, thus, the results of this study are very useful for developing scientific knowledge in the field of linguistics, especially for building a framework of thought about phenomena that appear in translation. Furthermore, through this research, it is hoped that there will be an inventory of the phenomenon of loss and gain of information in translation. The data is in the form of written data. In order to ensure the success of this research, data collection methods in the form of observation and note taking methods were applied in this study. The data were analyzed referring to the views of Nida (1975) on the Principles of Translation.